COVID-19: Current Status and Future Strategies to Control the Spread in the State of Tamil Nadu, India (Medico Legal Update, 2020)
The severe acute respiratory syndrome coronavirus 2 from the family of Coronaviridae is causing coronavirusdisease. This is a zoonotic disease and identified first in the Hubei Province of China. In early 2020, thisdisease was announced as a global pandemic. The pandemic hit the nations undiscriminating their economicand development status. Tamil Nadu, a state of India is one of the most affected in the country. In spite ofvarious precautionary measures in controlling the pandemic, the state recorded active cases of 18,881 as of13th June 2020. With no defined treatment to cure the disease till date, the healthcare workers along withthe collective support of various departments of the state are handling the situation with an aim to end theepidemic. Almost all the sectors such as finance, business, education, etc. were affected by the pandemic.This article discusses the current countermeasures for the infection, the impact on the state and suggests afew strategies to control the spread.